Synthesis, crystal structure and Hirshfeld surface analysis of a coordination compound of silver nitrate with 2-amino-benzoxazole - Razzoqova, Surayyo; Sadullayeva, Sojida; Erkinov, Sirojiddin; Torambetov, Batirbay; Alieva, Guloy; Yakhshieva, Zukhra; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E Crystallographic Communications, 2025)
The coordination complex of 2-amino-benzaxole (2AB) with silver(I), namely, bis(2-aminobenzoxazole-κ<i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">N)silver(I) nitrate-bis(2-aminobenzoxazole (1/2), [Ag(C<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">7H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">6N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2]NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3·2C<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">7H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">6N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O or [Ag(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2]NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3·(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2, was synthesized from ethanol solutions of AgNO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3 and 2AB. The asymmetric unit contains one mol-ecule of [Ag(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2]NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3·(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2, The central silver(I) atom is coordinated by two nitro-gen donor atoms from 2-amino-benzaxazole ligands in an N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2 coordination set while another two 2-amino-benzaxazole ligands and one nitrate anion remain uncoordinated. The crystal structure features several intra-molecular N-H⋯O and N-H⋯N hydrogen-bonding inter-actions as well as C-H⋯π, Ag⋯π and π-π inter-actions between adjacent AB ligands. Hirshfeld surface analysis and two-dimensional fingerprint plots were used to investigate the inter-molecular inter-actions.